2009
DOI: 10.1080/13854040801945060
|View full text |Cite
|
Sign up to set email alerts
|

Classification Accuracy and Predictive Ability of The Medical Symptom Validity Test's Dementia Profile and General Memory Impairment Profile

Abstract: When assessing symptom validity in patients with dementia, traditional approaches may be inappropriate because neurological factors may cause altered performance. The Medical Symptom Validity Test has a Dementia Profile that explicitly recognizes this fact. We prospectively evaluated classification accuracy of the Dementia Profile for 52 referrals to a memory disorders clinic. The Dementia Profile correctly classified 36/52 patients. Sensitivity was 54.8%, specificity was 90.5%, positive predictive value was 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 8 publications
1
44
1
Order By: Relevance
“…The respondent's scores are interpreted with reference to various clinical comparison groups and known profile configurations to determine the validity of the individual's effort. The test has been extensively validated in various clinical and nonclinical settings with populations ranging from normal children; to children with serious mental, cognitive, and behavioral disorders; to elderly patients with dementia; to those with mild to severe brain injury; and to other medical disability claimants (Blaskewitz, Merten, & Kathmann, 2008;Green, Flaro, & Courtney, 2009;Howe, Anderson, Kaufman, Sachs, & Loring, 2007;Howe & Loring, 2009;Richman et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The respondent's scores are interpreted with reference to various clinical comparison groups and known profile configurations to determine the validity of the individual's effort. The test has been extensively validated in various clinical and nonclinical settings with populations ranging from normal children; to children with serious mental, cognitive, and behavioral disorders; to elderly patients with dementia; to those with mild to severe brain injury; and to other medical disability claimants (Blaskewitz, Merten, & Kathmann, 2008;Green, Flaro, & Courtney, 2009;Howe, Anderson, Kaufman, Sachs, & Loring, 2007;Howe & Loring, 2009;Richman et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Two studies (Batt, Shores, & Chekaluk, 2008;Loring et al, 2011) using differing methodological approaches to temporarily Batt et al (2008) found greater reduction in performance on the WMT versus the TOMM in a traumatic brain injury (TBI) sample under a cognitive distraction task condition. From a clinical groups perspective, while it is welldocumented that some individuals with significant cognitive impairment (e.g., bilateral hippocampal atrophy; GoodrichHunsaker & Hopkins, 2009) can perform well on published PVTs, there is also a growing body of literature indicating that some moderate to severely impaired clinical groups with no incentive to malinger or supply poor effort produce unacceptably low specificity rates, and this appears to vary across individual PVTs (Gorissen, Sanz, & Schmand, 2005;Greve et al, 2008;Howe & Loring, 2009;Merten, Bossink, & Schmand, 2007;Rudman, Oyebode, Jones, & Bentham, 2011;Weinborn, Orr, Woods, Conover, & Feix, 2003;but cf. Chafetz, Prentkowski, & Rao, 2011;Schroeder & Marshall, 2010).…”
Section: Classification Accuracy Of the Forced-choice Recognition Memmentioning
confidence: 96%
“…Neither appears to match the WMT's exquisite sensitivity although they do exceed the TOMM (Green 2006(Green , 2007. The MSVT has several publications to its credit (Blaskewitz et al 2008;Carone 2008;Howe and Loring 2008;Stevens et al 2008) and offers an additional benefit over potential competitors: its subtests closely parallel the WMT's but are considerably easier. Performance levels on the MSVT that are lower than comparable scales on the WMT would be highly suspicious.…”
Section: Cognitive Symptom Validity Testsmentioning
confidence: 98%